Comparison between the Ethiopian Model of Cassation Division Binding Legal Interpretation and the Chinese Model of Guiding Case - Andargie, Haile (Bahir Dar University Journal of Law, 2022)
Both Ethiopia and China have introduced a system resembling a common law feature where the judiciary is involved in the development of case laws. This article is purported to compare and contrast the cassation model of Ethiopia and the Chinese guiding case system and to draw relevant lessons. Using doctrinal research methodology, the article examined relevant Ethiopian and Chinese laws, scholarly research findings and the literature in the field. After due analysis, the author concluded that China's guiding case system adopts a broad base of case selection systems involving the decision of lower courts whereas the Ethiopian system entirely depends on the Cassation division decision of the federal supreme court. In the Chinese system, both internal and external recommendation for a guiding case is allowed. The internal recommendation may come from various levels of courts besides the Supreme Court. Externally, the delegates of the lawmakers, experts, scholars, lawyers, and any other interested party could recommend a guiding case. Conversely, Ethiopia's system does not allow recommendations from other courts or an outsider stakeholder. Finally, China has detailed guidelines on the selection, recommendation, approval, and publication of a guiding case whereas Ethiopia's system lacks a comprehensive guideline. Therefore, this article argues that involving external recommenders, having an independent office and enacting detailed procedural directives are among the best practice that Ethiopia should learn from the Chinese guiding case system.